The Effect of Remuneration and BPJS Kesehatan on Work Ethic and Its Impact on Organizational Effectiveness at East Jakarta Metro Police (Polres Metro Jakarta Timur) - Ambarita DP (Privietlab, 2021)
Good organizational performance is essential for achieving institutional objectives, including in public sector organizations such as the East Jakarta Metro Police. High performance enables effective public service delivery and reflects overall organizational success. Performance, as a key determinant of organizational effectiveness, is influenced by various factors, including individual characteristics, job characteristics, and work environment conditions. This study aims to examine the extent to which remuneration and BPJS Kesehatan (health social security) influence work ethic and their subsequent impact on organizational effectiveness. Specifically, the study investigates: (1) the direct effect of remuneration on work ethic, (2) the direct effect of BPJS Kesehatan on work ethic, and (3) the direct effect of work ethic on organizational effectiveness at the East Jakarta Metro Police. Data were collected using both primary and secondary sources. Primary data were obtained from 90 respondents through questionnaires, supported by direct observation and literature review. The analysis employed both qualitative and quantitative approaches, with statistical testing conducted to determine the significance of the relationships among variables. The results indicate that remuneration and BPJS Kesehatan, both partially and simultaneously, have a positive and significant influence on work ethic. Furthermore, work ethic has a significant positive effect on organizational effectiveness. These findings suggest that strengthening employee welfare and work-related factors can enhance work ethic and ultimately improve organizational performance in the public sector.